Logistics: intermodalism - Prokop, Darren (Henry Stewart Talks, 2024)
Containers, Trailers, Lift-on, Lift-off (LoLo), Roll-on, Roll-off (RoRo), Drayage vehicles, Motor carriers, Port staging areas, Revenue, Economies of scale, Shipping capacity, Bill of lading, AI